Ultrasound assessment of small bowel Crohn's disease: A mixed methods exploration of barriers and facilitators to implementation in adult NHS IBD services - Radford, Shellie (2023)
Background: Crohn’s disease (CD) is a long-term condition which requires repeated disease monitoring via medical imaging, where repeated burdensome medical investigations negatively impact on patients quality of life. Small bowel ultrasound scanning (SBUS) has been shown to be similar in accuracy when compared to magnetic resonance enterography (MRE), has the potential to be quicker, less costly and improve patient experience of care, but it is not routinely used in NHS IBD care.